A Right to Read : Segregation and Civil Rights in Alabama's Public Libraries, 1900-1965 - Graham, Patterson Toby, 1969- (Book collections on Project MUSE., 2002)
A dramatic chapter in American cultural history. * Winner of the Alabama Library Association's Alabama Author Award for Nonfiction Patterson Toby Graham is Director of the Digital Library of Georgia at the University of Georgia in Athens.